Rancang Bangun Sistem Informasi Point of Sale (POS) Berbasis Web (Studi Kasus Toko Andorio) - Agus Mulyana; Uus Rusmawan (Majalah Ilmiah UNIKOM, 2023)
The sales management process that is currently running at the Andorio Store still uses traditional or conventional methods. This method is less efficient and effective because it involves the use of lots of notebooks and manual writing. Making reports is also time consuming because you have to copy data from sales receipts. The purpose of this research is to develop a Point Of Sale (POS) information system as a means to increase efficiency and effectiveness in the sales process and report generation at the Andorio Store. In this study, the application design method applied is the Waterfall method, Waterfall is one of the Software Engineering methods. The application design process is carried out sequentially, starting with conducting a needs analysis, designing the system, implementing and testing, implementing the program, and the last is maintenance. The programming language used is PHP, with MySQL database. The results of this study are a web-based Point Of Sale information system application that can be used to facilitate the operational activities of Andorio Stores starting from transaction processing such as purchases and sales, as well as facilitating report recapitulation such as purchase reports, sales and stock reports. Key Words : MYSQL, PHP, Point of sale, Waterfall